Nanopartículas de Nb2O5 aplicadas a células solares de perovskita - Assunção, João Pedro Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Currently, one of the most promising technologies in the field of photovoltaic devices are the so-called perovskite solar cells (CSPs). Its rapid advancement (today presenting more than 26% conversion efficiency) associated with its low production cost, make this technology highly attractive to the industrial sector. Despite their great progress, CSPs still face challenges that slow down their commercialization, the main ones being their scaling and long-term stability. Therefore, the present work proposes an alternative route for the production of Nb2O5 nanoparticles (NPs) and their application as an electron transport layer in CSPs, aiming to advance the issues surrounding the challenges of their commercialization. The results obtained show that self-suspended and crystalline Nb2O5 nanoparticles with dimensions of 20 nm were synthesized in times shorter than 15 minutes by the microwave-assisted hydrothermal method. The developed nanoparticles were applied as an electron transport layer in perovskite solar cells. The results obtained show that its application as compact films resulted in devices with a maximum efficiency (PCE) of 18.4%. For devices with mesoporous Nb2O5 films, the best devices presented a maximum PCE of 18.2%. The Nb2O5-based devices were compared with standard devices based on the compact Nb2O5 sol-gel layer and mesoporous TiO2, showing a maximum PCE of 18.1%. In general, the results indicate that solar cells prepared with compact Nb2O5 NP films with a concentration of 100 mg.mL-1 present optoelectronic and transport parameters similar to control cells, demonstrating that the route proposed in this work can be used in the production of High-efficiency CSPs compatible with devices demonstrated in the literature. The results also demonstrate that the application of two-bed Nb2O5 mesoporous films also produces parameters similar to those found in standard devices. On the other hand, the deposition of only one layer resulted in uncovered areas and devices that present high hysteresis. Furthermore, the capacitances in 1-layer devices are larger, suggesting that the observed hysteresis is promoted by charge accumulation in the uncovered areas.

Atualmente, uma das tecnologias mais promissoras no campo dos dispositivos fotovoltaicos são as chamadas células solares de perovskitas (CSPs). Seu rápido avanço (apresentando hoje mais de 26% de eficiência de conversão) associado ao seu baixo custo de produção, tornam essa tecnologia altamente atrativa ao setor industrial. Apesar de seu grande avanço, as CSPs ainda enfrentam desafios que retardam sua comercialização, sendo os principais seu escalonamento e sua estabilidade a longo prazo. Desta forma, o presente trabalho propõe uma rota alternativa para a produção de nanopartículas (NPs) de Nb2O5 e sua aplicação como camada transportadora de elétrons em CSPs, visando avançar nas questões que envolvem os desafios de sua comercialização. Os resultados obtidos mostram que nanopartículas autossuspensas e cristalinas de Nb2O5 com dimensões de 20 nm foram sintetizadas em tempos menores que 15 minutos pelo método hidrotermal assistido por micro-ondas. As nanopartículas desenvolvidas foram aplicadas em como camada transportadora de elétrons em células solares de perovskitas. Os resultados obtidos mostram que sua aplicação como filmes compactos resultaram em dispositivos com eficiência (PCE) máxima de 18,4%. Para dispositivos com filmes de Nb2O5 mesoporoso, os melhores dispositivos apresentaram PCE máxima de 18,2%. Os dispositivos baseados em Nb2O5 foram comparados com dispositivos padrão baseados na camada compacta de Nb2O5 sol-gel e TiO2 mesoporoso, apresentando PCE máxima de 18,1%. De maneira geral, os resultados apontam que células solares preparadas com filmes compactos NPs de Nb2O5 com concentração de 100 mg.mL-1 apresentam parâmetros optoeletrônicos e de transporte similares às células controle, demonstrando que a rota proposta neste trabalho pode ser utilizada na produção de CSPs de alta eficiência e compatíveis com dispositivos demonstrados na literatura. Os resultados também demonstram que a aplicação de filmes mesoporosos de Nb2O5 com duas camas também produzem parâmetros similares aos encontrados em dispositivos padrão. Por outro lado, a deposição de apenas uma camada resultou em áreas descobertas e dispositivos que apresentam alta histerese. Além disso, as capacitâncias em dispositivos de 1 camada são maiores, sugerindo que a histerese observada é promovida pelo acúmulo de carga nas áreas descobertas.
Nb2O5 nanoparticles applied to perovskite solar cells
Keywords: Células solares de perovskita; Camada compacta; Camada mesoporosa; Péntóxido de nióbio